Pathophysiology of Haemoptysis in Lung Disease - Airin Aldiani; Mohamad Fahmi Alatas (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Hemoptysis is expectoration of blood with or without sputum originating from the lower airway. Hemoptysis is an alarming symptom that couldlead to massive bleeding and life-threatening condition. Based on the underlying disease, hemoptysis can occur through several differentpathological mechanisms. Mostly, hemoptysis caused by bronchiectasis, pulmonary tuberculosis, lung cancer, and pulmonary fungalinfections. The incidence rate of the causative diseases can differ depending on its geographical location. Pulmonary vascularization consistsof two circulation pathways namely the pulmonary circulation and bronchial circulation, each of which has its own role. As many as 90% ofcases of hemoptysis are caused by collapse of the bronchial arteries, due to increased pressure in its circuit. It is important to understand thepathophysiology and pathomechanism of hemoptysis for further management on both diseases and also the clinical manifestasion.